Materials characterization of various lunar regolith simulants for use in geopolymer lunar concrete. Issue 11 (1st June 2022) - Collins, Peter J.; Edmunson, Jennifer; Fiske, Michael; Radlińska, Aleksandra
Abstract: Concrete materials are a feasible option for construction on the Moon utilizing the in-situ resources. An important part of any concrete material is the proper characterization of the raw materials to inform the mixture design and allow for interpretation of the end properties. Since lunar regolith simulants are the only near-term option for progressing the creation of a concrete material out of the lunar materials, it is important to use multiple simulant manufacturers to gain a well-rounded knowledge. In this study, five different lunar regolith simulants were characterized in detail and the data was used to create geopolymer concrete samples for compressive strength testing and subsequent microstructure analysis. Characterization results were also compared to available Apollo missions' sample data and discussed in terms of geopolymer lunar concrete. The 28-day compressive strength of the samples varied from 2653 psi to 7809 psi depending on the type of lunar regolith simulant. The lunar regolith simulants proved feasible for such concrete technology but exhibit variability due to their mineralogy, amorphous (glass) content, and particle size and shape distributions.